Cordyceps militaris extract induces apoptosis and pyroptosis via caspase‐3/PARP/GSDME pathways in A549 cell line. Issue 1 (30th October 2021) - Hu, Zixuan; Lai, Yijing; Ma, Chaoya; Zuo, Lina; Xiao, Guanlin; Gao, Haili; Xie, Biyuan; Huang, Xuejun; Gan, Haining; Huang, Dane; Yao, Nan; Feng, Baoguo; et al.
Abstract: Cordyceps militaris (CM) is traditionally used as dietary therapy for lung cancer patients in China. CM extract (CME) is hydrosoluble fraction of CM and extensively investigated. Caspase‐3‐involved cell death is considered as its major anticancer mechanism but inconclusive. Therefore, we explore its caspase‐3‐dependent programmed cell death nature (apoptosis and pyroptosis) and validate its caspase‐3‐dependent property in loss‐of‐function experiment. Component profile of CME is detected by High Performance Liquid Chromatography‐ quadrupole time‐of‐flight mass spectrometry (HPLC‐qTOF). Results show that CME causes pyroptosis‐featured cell bubbling and cell lysis and inhibits cell proliferation in A549 cell. CME induces chromatin condensing and makes PI+/annexin V+ staining in bubbling cells, indicating genotoxicity, apoptosis, and pyroptosis cell death are caused by CME. High concentration of CME (200 μg/ml) exerts G2/M and G0 cell cycles arresting and suppresses P53‐downstream proliferative proteins, including P53, P21, CDC25B, CyclinB1, Bcl‐2, and BCL2 associated agonist of cell death (BAD), but 1–100 μg/ml of CME show less effect on proteins above. Correspondingly, caspase‐3 activity and caspase‐3 downstream proteins including pyroptotic effector gasdermin‐E (GSDME) and apoptotic marker cleaved‐poly‐ADP‐ribose polymerase (PARP) are significantly promoted by CME. Moreover, regarding membrane pore formation in pyroptotic cell, expression of membrane GSDME (GSDME antibody conjugated with PE‐Cy7 for detection in flow cytometry) is remarkably increased by CME treatment. By contrast, other pyroptosis‐related proteins such as P2X7, NLRP3, GSDMD, and Caspase‐1 are not affected after CME treatment. Additionally, TET2 is unexpectedly raised by CME. In present of caspase‐3 inhibitor Ac‐DEVD‐CHO (Ac‐DC), CME‐induced cytotoxicity, cell bubbling, and genotoxicity are reduced, and CME‐induced upregulation of apoptosis (cleaved‐PARP‐1) and pyroptosis (GSDME‐NT) proteins are reversed. Lastly, 22 components are identified in HPLC‐qTOF experiment, and they are classified into trophism, neoadjuvant component, cytotoxic component, and cancer deterioration promoter according to previous references. Conclusively, CME causes caspase‐3‐dependent apoptosis and pyroptosis in A549 through caspase‐3/PARP and caspase‐3/GSDME pathways, and it provides basic insight into clinic application of CME for cancer patients. Abstract : The present study has shown that the Cordyceps militaris extract CME exerts both apoptosis and pyroptosis toward A549 cell line through inducing caspase‐3‐depended pyroptosis and apoptosis.